UPAYA MENINGKATKAN KETERAMPILAN BERDOA SISWA MELALUI PENDEKATAN PRAKTIK DI SD NEGERI 025 SIABU - Rahmadhani, Rahmi; Idham Hasibuan, Marlina, (PANTAK: Jurnal Penelitian Tindakan Kelas, 2024)
This study aims to improve the prayer skills of fourth grade students of SD Negeri 025 Siabu through a practical approach in two learning cycles. Participants consisted of 30 students who showed significant development in their prayer skills. In the initial test, the average score of students' prayer skills was 60%, but after cycle I, the average score increased to 75%, and in cycle II, the average score reached 90%, with a total increase of 30%. Student involvement in learning also increased, from 80% in cycle I to 90% in cycle II. Most students felt more confident in praying, with 85% of students showing a confident and solemn attitude in praying in cycle II, an increase compared to 60% at the beginning of the study. Interviews with students and teachers revealed that the practical approach helped students memorize prayers more easily, increased their self-confidence, and increased interest in learning Islamic Religious Education. Based on these results, it can be concluded that the practical approach is effective in improving students' prayer skills and can be applied to improve the quality of Islamic Religious Education learning in elementary schools.